CT of the head for acute stroke: Diagnostic performance of a tablet computer prior to intravenous thrombolysis. Issue 3 (3rd February 2017) - McLaughlin, Patrick D; Moloney, Fiachra; O'Neill, Siobhan B; James, Karl; Crush, Lee; Flanagan, Oisin; Maher, Michael M; Wyse, Gerald; Fanning, Noel
Abstract: Introduction: The authors propose that tablet computers could benefit patients with acute stroke in the remote care setting, where time to and accuracy of CT interpretation greatly influences patient outcome. Methods: One hundred and fifty consecutive patients who presented to the Emergency Department of a tertiary referral neurosciences centre within a time window suitable for intravenous thrombolytic therapy were included. Images were wirelessly transmitted to a tablet computer (iPad 3rd Generation, model = A1430, Apple, Cupertino, CA) and were reviewed by radiologists with three levels of experience for signs of intracranial haemorrhage, large vessel occlusion and parenchymal infarction. Reference standard interpretation was performed by two neuroradiologists using a diagnostic monochrome display. Results: Consensus neuroradiologist review on the tablet display found and correctly classified all of the 23 cases of intracranial haemorrhage including 21 cases of parenchymal haematoma, two cases of petechial haemorrhage and one patient with an acute subdural haematoma. Less experienced readers missed cases of petechial and subdural haematomas. There was excellent agreement between the tablet and diagnostic monochrome display in cases with no infarct or extensive parenchymal infarction. Conclusions: Tablet computers can be used to facilitate rapid preliminary CT interpretation in patients with acute stroke in the remote setting.